Segmented worms (Phylum Annelida): a celebration of twenty years of progress through Zootaxa and call for action on the taxonomic work that remains - Magalhães, Wagner F.; Hutchings, Pat; Oceguera-Figueroa, Alejandro; Martin, Patrick; Schmelz, Rüdiger M.; Wetzel, Mark J.; Wiklund, Helena; Maciolek, Nancy J.; Kawauchi, Gisele Y.; Williams, Jason D. (Zootaxa, 2021)
Zootaxa has been the leading journal on invertebrate systematics especially within Annelida. Our current estimates indicate annelids include approximately 20,200 valid species of polychaetes, oligochaetes, leeches, sipunculans and echiurans. We include herein the impact of Zootaxa on the description of new annelid species in the last two decades. Since 2001, there have been over 1,300 new annelid taxa published in about 630 papers. The majority of these are polychaetes (921 new species and 40 new genera) followed by oligochaetes (308 new species and 10 new genera) and leeches (21 new species). The numerous papers dealing with new polychaete species have provided us a clear picture on which polychaete families have had the most taxonomic effort and which authors and countries have been the most prolific of descriptions of new taxa. An estimated additional 10,000+ species remain to be described in the phylum, thus we urge annelid workers to continue their efforts and aid in training a new generation of taxonomists focused on this ecologically important group.